Synthesis and electropolymerization of EDOT modified 1,3-bis(5-methyl-2-thiazolylimino)isoindolinato palladium(II) complex for electrochemical detection of hydrogen peroxide - KOCA, ATIF (TAYLOR & FRANCIS LTD, 2017)
1,3-Bis(5-methyl-2-thiazolylimino) isoindoline derivative (EDOT-BTI) containing an electropolymerizable group is prepared using the Linstead method. According to this two-step method phthalonitrile derivative EDOT-Pht is converted to 1,3-diiminoisoindoline EDOT-DII first then EDOT-DII is reacted with 2-amino-5-methylthiazole in ethanol during 5day reflux. Palladium(II) complex (EDOT-PdBTI) of EDOT-BTI is synthesized in benzene using [Pd(PhCN)(2)Cl-2] as the palladium(II) precursor and triethylamine as auxiliary base. In order to show the H2O2 sensing properties of EDOT-PdBTI, electrochemical characterizations of EDOT-BTI and EDOT-PdBTI are performed and then modified glassy carbon electrode is constructed with electropolymerization of EDOT-PdBTI. GCE/PEDOT-PdBTI shows a wave at 0.215V. With increasing H2O2 concentration, this wave shifts to -0.075V. A linear range is observed between 0.72 and 13.6moldm(-3) with a limit of detection of 0.21moldm(-3) and sensitivity of 0.0153mVmol(-1)dm(-3). These data illustrate possible use of the electrode as a potentiometric H2O2 sensor. [GRAPHICS] .
Keywords: Electropolymerization; EDOT; hydrogen peroxide; 1,3-Bis(2-thiazolylimino)isoindoline; palladium; CATALASE MIMICS; MANGANESE(II) COMPLEX; H2O2; ISOINDOLINE; LIGANDS; GLUCOSE; SENSOR; FILM